Further evidence that de novo missense and truncating variants in ZBTB18 cause intellectual disability with variable features. Issue 5 (10th October 2016) - Cohen, J.S.; Srivastava, S.; Farwell Hagman, K.D.; Shinde, D.N.; Huether, R.; Darcy, D.; Wallerstein, R.; Houge, G.; Berland, S.; Monaghan, K.G.; Poretti, A.; Wilson, A.L.; et al.
Abstract : Identification of rare genetic variants in patients with intellectual disability (ID) has been greatly accelerated by advances in next generation sequencing technologies. However, due to small numbers of patients, the complete phenotypic spectrum associated with pathogenic variants in single genes is still emerging. Among these genes is ZBTB18 ( ZNF238 ), which is deleted in patients with 1q43q44 microdeletions who typically present with ID, microcephaly, corpus callosum (CC) abnormalities, and seizures. Here we provide additional evidence for haploinsufficiency or dysfunction of the ZBTB18 gene as the cause of ID in five unrelated patients with variable syndromic features who underwent whole exome sequencing revealing separate de novo pathogenic or likely pathogenic variants in ZBTB18 (two missense alterations and three truncating alterations). The neuroimaging findings in our cohort (CC hypoplasia seen in 4/4 of our patients who underwent MRI) lend further support for ZBTB18 as a critical gene for CC abnormalities. A similar phenotype of microcephaly, CC agenesis, and cerebellar vermis hypoplasia has been reported in mice with central nervous system‐specific knockout of Zbtb18 . Our five patients, in addition to the previously described cases of de novo ZBTB18 variants, add to knowledge about the phenotypic spectrum associated with ZBTB18 haploinsufficiency/dysfunction. Abstract :